2012
DOI: 10.4049/jimmunol.1102538
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Stat3 Induces Senescence in Tumor Cells and Elicits Prophylactic and Therapeutic Immune Responses against Breast Cancer Growth Mediated by NK Cells and CD4+ T Cells

Abstract: Aberrant Stat3 activation and signaling contribute to malignant transformation by promoting cell cycle progression, inhibiting apoptosis, and mediating tumor immune evasion. Stat3 inhibition in tumor cells induces the expression of chemokines and proinflammatory cytokines, so we proposed to apply Stat3-inhibited breast cancer cells as a source of immunogens to induce an antitumor immune response. Studies were performed in two murine breast cancer models in which Stat3 is activated: progestin-dependent C4HD cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…It was demonstrated by different approaches (fluorimetry, flow cytometry, and confocal microscopy) that U-Omp19 partially inhibits cathepsin L activity inside live DC lysosomes. Moreover, U-Omp19 inhibits cathepsin L activity inside live mature DCs (LPS treated), indicating that observed inhibition by U-Omp19 is not an indirect consequence of changes undertaken by DCs during maturation (29).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It was demonstrated by different approaches (fluorimetry, flow cytometry, and confocal microscopy) that U-Omp19 partially inhibits cathepsin L activity inside live DC lysosomes. Moreover, U-Omp19 inhibits cathepsin L activity inside live mature DCs (LPS treated), indicating that observed inhibition by U-Omp19 is not an indirect consequence of changes undertaken by DCs during maturation (29).…”
Section: Discussionmentioning
confidence: 86%
“…Three weeks later, immunized mice were injected s.c. in the right flank with 1 3 10 5 MO5 cells (B16 murine melanoma cells expressing OVA). Animals were monitored and tumor growth was measured three times a week as described previously (29).…”
Section: Adoptive Transfer Of Ot-i Cells and In Vivo Cd8 + T Cell Promentioning
confidence: 99%
“…That is, exploitation of methods to evade cellular senescence and restore deregulated autophagy and inappropriate biliary innate immunity could be a promising approach for treating these intractable cholangiopathies. A therapeutic approach to these processes require a clear understanding of its regulation, particularly the signaling related to ATK/mTOR and p53 which are implicated in the process of senescence, autophagy and apoptosis [30][31][32]54,55,143,144]. Furthermore, challenges to detect differences and similarities of the disease processes in these fibrosing cholangiopathies are also informative in the evaluation of their unique pathogenesis.…”
Section: Participation Of Innate Immunitymentioning
confidence: 97%
“…It has been reported that the inactivation of STAT3 in tumor cells favored NK-cell-and T-cell-mediated antitumor immune responses (19)(20)(21); however, whether NK cell function can be augmented by blocking STAT3 in human hepatocellular carcinoma cells has not been fully investigated. In this study, we focus on NK-cell-mediated antitumor immune responses to STAT3-blocked hepatocellular carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%